2018
DOI: 10.3389/fpls.2018.01107
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore-Associated Bacteria as Potential Mediators and Modifiers of Induced Plant Defense Against Spider Mites and Thrips

Abstract: Induced plant defense, comprising contact with exogenous stimuli, production of endogenous signals alerting the plant, associated biochemical cascades, and local and/or systemic expression of the defense mechanisms, critically depends on the nature of the inducing agents. At large, bio-trophic pathogenic microorganisms and viruses usually trigger the salicylate (SA)-mediated pathway, whereas necro-trophic pathogens and herbivores usually trigger the jasmonate (JA)-mediated pathway in plants. The SA- and JA-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…These features support the mite polyphagous character and demonstrate its capability to counteract the effects of a variety of active components either synthesized by the plant as defenses or as components of the acaricides used for pest control. In addition, the presence of endosymbionts, mainly Wolbachia spp, in spider mites may alter their interaction with the host, manipulate the plant defenses and modify mite performance [19,20]. Biological control of spider mites through natural predators is a useful practice in closed greenhouses but not in open fields.…”
Section: Introductionmentioning
confidence: 99%
“…These features support the mite polyphagous character and demonstrate its capability to counteract the effects of a variety of active components either synthesized by the plant as defenses or as components of the acaricides used for pest control. In addition, the presence of endosymbionts, mainly Wolbachia spp, in spider mites may alter their interaction with the host, manipulate the plant defenses and modify mite performance [19,20]. Biological control of spider mites through natural predators is a useful practice in closed greenhouses but not in open fields.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that red spider mite‐infested coffee plants were more resistant to conspecifics and the coffee leaf miner Leucoptera coffeella Guérin‐Méneville (Lepidoptera: Lyonetiidae), although these results contrasted with observations in the field, where multiple infestations by the two herbivores were frequently found. Inconsistencies in mite‐induced plant responses have been commonly reported in the literature as the ability of mites to manipulate plant defences seems to vary among populations and might be related to their associated bacteria (Schausberger, ). Therefore, the questions of whether red spider mites suppress coffee plant defences, and whether this ability varies among populations, deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…More studies are needed to determine the mechanisms by which Herbivore-associated bacteria regulate JAinducible plant defenses (Frago et al, 2012). Further studies to achieve selective elimination of single bacterial taxa, to pinpoint which bacteria are responsible for manipulating plant defense (Schausberger, 2018). Physiological and genetic studies are needed to directly demonstrate the role of microbes in assisting detoxification in insect gut (Sikano et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Microbes have persistent associations with their hosts and that do not cause overt pathogenic symptoms. Insect symbionts can be divided into three general categories based on their location relative to the insect body: environmental (or external), digestive system (internal extracellular) and endosymbionts (internal intracellular) (Schausberger, 2018). Few symbionts are intracellular or housed within the body cavity and are passed between generations through eggs, resulting in maternal inheritance.…”
Section: Categories Of Symbiontmentioning
confidence: 99%